Local voices call for economic development over forest conservation: Trade-offs and policy in Bungo, Sumatra - Feintrenie, L.; Levang, P. (2011)
Local communities, especially those living in forested areas, are generally presented as innocent victims of global economic policies that benefit the private and public sectors. This paper discusses local stakeholders’ perception of the government policies and actions, people’s rights, and people’s participation in decision-making, with a focus on land and forest uses. It is based on a perception survey conducted in 2009 in 12 villages of the Bungo district, (Jambi province, Sumatra, Indonesia), and semi-directed interviews of representatives of the regional government. The surveys conclude to a good agreement between local people and the different levels of government. Besides, villagers consider that their voice is well taken into account in decision-making processes. And over all, there is a broad consensus among all stakeholders to favour economic development at the expense of forest conservation.